Chromatin Accessibility Dynamics during iPSC Reprogramming - Li, Dongwei; Liu, Jing; Yang, Xuejie; Zhou, Chunhua; Guo, Jing; Wu, Chuman; Qin, Yue; Guo, Lin; He, Jiangping; Yu, Shenyong; Liu, He; Wang, Xiaoshan; et al. (Cell stem cell, 2017)
Cell-fate decisions remain poorly understood at the chromatin level. Here, we map chromatin remodeling dynamics during induction of pluripotent stem cells. ATAC-seq profiling of MEFs expressing Oct4-Sox2-Klf4 (OSK) reveals dynamic changes in chromatin states shifting from open to closed (OC) and closed to open (CO), with an initial burst of OC and an ending surge of CO. The OC loci are largely composed of genes associated with a somatic fate, while the CO loci are associated with pluripotency. Factors/conditions known to impede reprogramming prevent OSK-driven OC and skew OC-CO dynamics. While the CO loci are enriched for OSK motifs, the OC loci are not, suggesting alternative mechanisms for chromatin closing. Sap30, a Sin3A corepressor complex component, is required for the OC shift and facilitates reduced H3K27ac deposition at OC loci. These results reveal a chromatin accessibility logic during reprogramming that may apply to other cell-fate decisions. [Display omitted] •ATAC-seq reveals chromatin accessibility dynamics during reprogramming•TFs associated with initial chromatin closing are barriers for reprogramming•OSK opens the pluripotent loci gradually through a direct process•OSK closes the somatic loci indirectly in part through SAP30 Li et al. show that Yamanaka factors remodel the nuclear architecture of MEFs following a binary logic that may guide further improvement in reprograming technology and be applicable for other cell-fate decisions.